(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Since the evolvement of human from primitive times to the development of modern civilized societies of today, education has remained a basic element of human thought process and a fulcrum of a large part of social activities. By knowing this, in the present study we highlight the generating confusion among Educational Institutions in which the continuous and comprehensive evaluation pattern and sociological perspectives of education were detailed studied.